Plesionika edwardsii - Olthof, Gabriël; Becking, Leontine E.; Fransen, Charles H. J. M. (Zenodo, 2018)
Plesionika edwardsii (Brandt, 1851) Pandalus Guerinii Risso, 1844: 95. [nomen nudum] Pandalus ( Pontophilus ) Edwardsii Brandt, 1851: 122; nomen novum for Pandalus narval H. Milne Edwards, 1841 [in H. Milne Edwards, 1836–1844], nec Astacus Narval Fabricius, 1787. [Mediterranean, type locality designated by Chan & Yu, 1991] Pandalus ( Parapandalus ) longirostris Borradaile, 1900: 413; Plate 37, fig. 10a–h. [New Britain] Plesionika edwardsii Chan & Crosnier 1997: 193 –194, fig. 23; Fransen 2014b: 176–177. Material examined. RMNH. CRUS.D.57269: 1 specimen, total length 18cm, Curaçao, depth 299m (980ft), 16.xii.2015, dive with submersible Curasub, collected by A. ‘Dutch’ Schrier. RMNH. CRUS.D.57270: 1 specimen, Curaçao, 12°05'03"N 68°53'55"W, depth 299m (980ft), 9.ii.2017, dive with submersible Curasub, collected by A. ‘Dutch’ Schrier & Gabriel Olthof. Distribution. Western Atlantic: South Carolina, USA, Bahamas, Cuba west to Gulf of Mexico, south to Suriname, including the Antilles. Eastern Atlantic: from northwest Spain south to Sierra Leone (some records as far south as Angola); Mediterranean, except the Adriatic and the Black Seas. Also recorded from the Red Sea and Indian Ocean and Indo-West Pacific, as far as Indonesia and the Philippines. Remarks. The present specimens fit the diagnoses given by Fransen (2014b). Published as part of Olthof, Gabriël, Becking, Leontine E. & Fransen, Charles H. J. M., 2018, On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea, pp. 533-548 in Zootaxa 4415 (3) on page 537, DOI:10.11646/zootaxa.4415.3.7, http://zenodo.org/record/1242209